THE EFFECTIVENESS OF HEALTH EDUCATION IN INCREASING PUBLIC KNOWLEDGE ABOUT NON-COMMUNICABLE DISEASES AS AN EARLY PREVENTION EFFORT - Jeini Ester Nelwan; Oksfriani Jufri Sumampouw (International Journal of Multidisciplinary Reseach, 2026)
Non-communicable diseases (NCDs) are the leading cause of mortality worldwide and represent a major challenge to public health development, including in Indonesia. The high prevalence of NCDs such as hypertension, diabetes mellitus, and cardiovascular diseases is closely associated with low levels of public awareness and unhealthy lifestyle behaviors. Therefore, promotional efforts through health education are essential strategies to enhance community knowledge and awareness regarding NCD prevention. This community service activity aims to improve public knowledge of non-communicable diseases and their prevention through health education interventions. The implementation method employed an educational approach through health counseling , accompanied by pre-test and post-test assessments to measure participants' knowledge before and after the intervention. The materials delivered included the definition of NCDs, risk factors, health impacts, and preventive measures through clean and healthy lifestyle behaviors . The educational sessions were conducted interactively using lectures, discussions, and question-and-answer sessions. The results showed that prior to the intervention, the majority of participants (93.3%) already had a good level of knowledge. After the health education intervention, this increased to 100% of participants achieving a good knowledge category. Additionally, participants demonstrate high enthusiasm during the activity, as reflected in their active participation in discussions and their ability to respond to questions related to the materials presented. In conclusion, health education counseling proved to be effective in improving community knowledge regarding non-communicable diseases. This improvement in knowledge is expected to serve as a foundation for promoting sustainable healthy behavior changes. However, follow-up efforts such as continuous mentoring and evaluation are necessary to ensure the practical implementation of knowledge in daily life in order to reduce the incidence of NCDs in the community.